The Implementation of Integrated Technology in Motivating Students of an Accelerated Program at Senior Secondary School Makassar, Indonesia - Muhammad Irfan Rahim; Kisman Salija; Sukardi Weda (ELT Worldwide: Journal of English Language Teaching, 2016)
The objectives of this research are to find out: (1) the description of the implementation of integrated technology in an accelerated program in motivating the students in Makassar senior secondary school, (2) the description of how the teacher maintains the motivation of students through integrated technology at accelerated program in Makassar senior secondary school, and (3) the description of the students’ responses to the implementation of integrated technology in an accelerated program in motivating the students in Makassar senior secondary school.This research is qualitative research which done inSMAN17 Makassar. The participants of this research were a teacher and students of an accelerated program. To collect the data, the researcher used recording and interview with the teachers and students. In analysing the data, the researcher used qualitative method. The findings of this research described (1) The implementation of integrated technology at the accelerated program in SMAN 17 Makassar can be described under several categories: kinds of technology used by the teacher, kinds of application or program used by the teacher, the function of technology, the teacher’s ways to teach by using technology, the teacher’s experience in achieving the technology used, the technology facilitation provided in technology integration, the teacher’s ways in teaching English skills, the use of social media in teaching and learning, the reason of choosing E-Mail, the teacher’s ways to minimize unexpected problem along the use of technology, and the technology influence toward student’s motivation (2) The teacher’s ways to maintain the students’ motivation by using integrated technology can be described two some categories: the reasons underlying the importance of technology and the teacher’s ways of indicating and maintaining the students’ motivation. (3) Students’ responses toward the integrated technology could be stated in positive way, they liked it, they were interested, and they preferred studying by using technology. Keyword: Integrated Technology and Students’ Motivation